Long Bus Vehicle Rear Swing Out Impact Assessment Using On-Board Video Camera - Muhamad Shaharudin Osmin; Jezan Md Diah; Sariwati Mohd Sharif; Wan Mazlina Wan Mohamed; Nur Quratul Aini Hamidun (International Journal of Supply Chain Management, 2017)
The current maximum allowable overall length of bus for Malaysia is only 12.2 m. However, the government had gazetted the United Nations Regulation (UNR) 107 and due to be implemented in July 2017. The implementation of UNR107 among others will allow the use of bus for overall length more than 12.2 m.This study investigates the manoeuvrability of single rigid, 15-metre bus based on its rear swing out impact. The rear swing out impact assessment of longer bus (15-metre) was made by recording a video from a video camera mounted on the rear, pointing rearward of a single rigid, 12-metre bus during manoeuvre. The video camera view angle was set to represent the excessive 3 m of longer bus and any infrastructures that appeared in the view were identified as the possible impact. From the video recording, it was found that longer bus will have a minimal manoeuvrability issues on the road. However, modification may be needed specifically at tight intersection or small roundabout to allow a smooth manoeuvrability of longer bus.